New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae) - Ustjuzhanin, Petr; Kovtunovich, Vasily; Sáfián, Szabolcs (Zootaxa, 2017)
There have been no special studies on plume moths of Liberia until recently. In the World Catalogue of Insects (Gielis 2003) only two species are reported from Liberia: Agdistis tamaricis (Zeller, 1847) and Megalorhipida leucodactyla (Fabricius, 1794) despite its well-known richness for other Lepidoptera groups (Fox et al. 1965, Larsen 2005) and its biogeographic position in the centre of the Upper Guinean biodiversity hotspot (Myers et al. 2000).